Implementasi Pembelajaran Tematik Berdasarkan Standar Proses Pendidikan di Madrasah Ibtidaiyah (Studi Kasus di MIN 1 Bantul) - Laelatul Badriah (Universitas Alma Ata, 2018)
Education is an important pillar in creating a dignified nation's successor. Education in Indonesia has set a national education standard (SNP) that has long been applied in the education bureaucracy in Indonesia. MIN 1 Bantul is one of the Madarsah who has applied thematic learning based on the implementation of the 2013 Curriculum both in planning, implementation and evaluation. In addition, MIN 1 Bantul also includes madrasas that have implemented management in accordance with national education standards. Some important things in this study are the madrasa which tends to be the number two education, the implementation of educational standards that have not been maximized, and the fulfillment of process standards in the learning process at madrasah educational institutions.Keywords: thematic learning, madrasah management, process standards